2010
DOI: 10.1371/journal.pgen.1000774
|View full text |Cite
|
Sign up to set email alerts
|

A Major Role of the RecFOR Pathway in DNA Double-Strand-Break Repair through ESDSA in Deinococcus radiodurans

Abstract: In Deinococcus radiodurans, the extreme resistance to DNA–shattering treatments such as ionizing radiation or desiccation is correlated with its ability to reconstruct a functional genome from hundreds of chromosomal fragments. The rapid reconstitution of an intact genome is thought to occur through an extended synthesis-dependent strand annealing process (ESDSA) followed by DNA recombination. Here, we investigated the role of key components of the RecF pathway in ESDSA in this organism naturally devoid of Rec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
145
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 138 publications
(148 citation statements)
references
References 72 publications
2
145
1
Order By: Relevance
“…Consistent with this view, UvrD-a SF1 type helicase-is implicated in RDR in Deinococcus radiodurans. 39 In yeast, the replicative hexameric MCM helicase is likely to be loaded at D-loops during BIR. 40 However, BIR is only decreased by ~4-5 fold in the absence of MCM activity, suggesting that other potentially nonprocessive helicases may also function in this pathway, which could conceivably reduce the fidelity of RDR.…”
Section: Perspectives On Error-prone Rdrmentioning
confidence: 99%
“…Consistent with this view, UvrD-a SF1 type helicase-is implicated in RDR in Deinococcus radiodurans. 39 In yeast, the replicative hexameric MCM helicase is likely to be loaded at D-loops during BIR. 40 However, BIR is only decreased by ~4-5 fold in the absence of MCM activity, suggesting that other potentially nonprocessive helicases may also function in this pathway, which could conceivably reduce the fidelity of RDR.…”
Section: Perspectives On Error-prone Rdrmentioning
confidence: 99%
“…Later, it was shown that recF mutants are even more hypersensitive to UV radiation than RecBC, that RecF pathway plays a major role in replication restart under UV damage conditions, and that RecF is involved in DSBs repair in the absence of RecBC and SbcBC (Clark, 1991;Courcelle, 2005;Courcelle et al, 1997;Ivancic-Bace et al, 2003;Kidane et al, 2004;Kusano et al, 1989;Whitby and Lloyd, 1995;Zahradka et al, 2006). Sequencing of new genomes revealed the ubiquitous nature of RecF pathway proteins found in most bacteria (Rocha et al, 2005), including the radiation resistant bacteria Deinococcus radiodurans (Bentchikou et al, 2010;Cox et al, 2010;Chang et al, 2010;Makarova et al, addition to initial loading of RecA, RecOR further stimulate homologous recombination by preventing the dissociation of RecA* filament from ssDNA in E. coli (Bork et al, 2001). Somewhat different properties were reported for Bacillus subtilis RecO, which does not require RecR for initiation of RecA* formation (Manfredi et al, 2008;Manfredi et al, 2010).…”
Section: Recf Pathwaymentioning
confidence: 99%
“…Unlike the addA (recB) mutant, the recR and recO mutants did not show significant sensitivity to ionizing radiation (IR) and to mitomycin C [68,71], suggesting that RecRO pathway is not responsible for repairing DNA damage induced by these agents, most likely double strand breaks. This is in contrast to E. coli where the RecFOR pathway sometimes substitutes for the RecBCD pathway and in Deinococcus radiodurance where the RecFOR pathway plays a major role in double strand break repair [98,99]. On the other hand, H. pylori recR and recO mutants were shown to be much more sensitive to oxidative stress and to acid stress than the wild type strain [71], indicating that H. pylori RecRO pathway is involved in repairing DNA damage induced by these stress conditions.…”
Section: H Pylori Recro Pathwaymentioning
confidence: 99%